Integration processes in Latin America - Landa Arroyo, César (2023)
After the fall of the Berlin Wall and the so-called “Washington Consensus”, the United States promoted the Free Trade Area of the Americas (LAC) with Canada and Mexico, the same one that managed to spread through Central America and some South American countries through some Free Trade Agreements; while in the Southern Hemisphere the Southern Common Market (Mercosur) was constituted that unites Brazil, Argentina, Integration processes are dynamic insofar as politics and the economy are interdependent factors not only at the local level, but also at the international level. Therefore, it isimportant to highlight what are the factors or constitutive dimensions of sub regional integration processes.